Structural, functional and comparative genomics of Nile tilapia (Oreochromis niloticus) - Bueno, Laura (2024)
Nile tilapia stands out in aquaculture due to its adaptability to freshwater and brackish water environments. The significant advance in the area of ​​genomics culminated in the sequencing and annotation of the genome of Oreochromis niloticus, submitted by the University of Maryland in 2019. The present study aims to present structural, functional and comparative aspects of the genome of this species, through the use of genomic databases, focusing on the growth hormone (GH) gene. Genomic associative studies allowed the identification of another five genes related to growth. Phylogenetic analysis revealed the evolution of this gene in several species, while functional and comparative genomics point to the need for greater characterization of the relationships between genes.